INDONESIAN TRADE PROMOTION CENTER (ITPC) DIPLOMACY IN ENCOURAGING COFFEE EXPORTS TO THE UNITED STATE AS ECONOMIC RECOVERY FOR 2021-2022 - Lutfia Fiki (Mediasi: Journal of International Relations, 2021)
Coffee is Indonesia's leading export commodity that is able to create added value for the country's foreign exchange. The Covid-19 pandemic that entered Indonesia has caused a decrease in coffee exports to the United States. One of the government's agendas to create economic recovery is carried out by optimizing the Indonesian Trade Promotion Center (ITPC) to emphasize the task of diplomacy. This study analyzes the role of ITPC in encouraging coffee exports to the United States as an effort to accelerate economic recovery. The research method used is qualitative explorative by relying on secondary data. The concept used is commercial diplomacy according to Michel Kostechky and Ollivier Naray which emphasizes the value chain which includes the main activities that include (trade promotion, FDI promotion, science and technology cooperation, tourist promotion and advocacy of the national business community) and support activities that include (intelligence, networking and public relations, negotiation contacts and problem solving). ITPC's efforts in encouraging coffee exports to the United States are based on the main activities, namely through trade promotion strategies and providing business advocacy services. Indicators of FDI promotion, science and technology cooperation and tourist promotion are not run by ITPC Los Angeles and ITPC Chicago because they do not fall within the authority and duties of ITPC. While efforts in support activities consist of intelligence, networking and public relations. Contact indicators of negotiation and problem resolution are not the authority of ITPC so they are not carried out. The results of ITPC's performance in encouraging coffee exports can be seen through an increase in the value of coffee exports to the United States in 2021-2022.